The blighted stars - O'Keefe, Megan E., 1985- (O'Keefe, Megan E., 1985- Devoured worlds, 2023)
"She's a revolutionary. Humanity is running out of options. Habitable planets are being destroyed as quickly as they're found, and Naira Sharp thinks she knows the reason why. The all-powerful Mercator family has been controlling the exploration of the universe for decades, and exploiting any materials they find along the way under the guise of helping humanity's expansion. But Naira knows the truth, and she plans to bring the whole family down from the inside. He's the heir to the dynasty. Tarquin Mercator never wanted to run a galaxy-spanning business empire. He just wanted to study geology and read books. But Tarquin's father has tasked him with monitoring the settlement of a new planet, and he doesn't really have a choice in the matter. Disguised as Tarquin's new bodyguard, Naira plans to destroy the settlement ship before they make land. But neither of them expects to end up stranded on a dead planet. To survive and keep her secret, Naira will have to join forces with the man she's sworn to hate. And together they will uncover a plot that's bigger than both of them"--